(untitled) (Texas Journal of Medical Science, 2023)
It is characterized by polymorphic rashes in the form of erythema, target-shaped papules, which can progress to vesicular and bullous lesions, on the site of which erosions form. Rashes are mainly localized on the hands, feet, upper and lower extremities. Mucosal involvement may occur. Erythema multiforme is a polyetiological disease mainly based on hypersensitivity reactions to drugs or infection, but in some cases associated with other pathological conditions, in particular with Kawasaki disease [68]. Treatment of patients is based on the withdrawal of causative drugs or the treatment of existing infectious diseases. In some cases, the course is recurrent, which is due to unresolved antigenic stimulation